Implementation of Nonlinear Finite Element Using Object–Oriented Design Patterns - Yaghoobi, A. (Journal of Mechanical Engineering and Technology (JMET), 2015)
This paper concerns with the aspects of the object–oriented programming used to develop a nonlinear finite element for the analysis of plates based on Reissner–Mindlin theory. To study the shear locking problem in thin plates which occurs in the case of using Full integration method, three kinds of finite elements namely Bilinear, Serendipity and Lagrange with Full, Reduced and Selective Reduced integration methods, are used. By implementing three design patterns of Model–Analysis Separation, Model–UI Separation and Modular Analyzer in the code, the reusability and the extendibility of the program in adding new elements with different number of nodes and integration methods have been increased.